Monetary policy, bank competition and regional credit cycles: Evidence from a quasi-natural experiment - Segev, Nimrod; Schaffer, Matthew (Journal of Corporate Finance, 2020)
This paper examines how competition in the banking sector affects the transmission of monetary policy and the variation of credit expansion across regions in the United States. Using the U.S. branching deregulation between 1994 to 2008 as an exogenous change in banks’ competition, we analyze how bank competition affects monetary policy transmission through the bank lending channel. The results show that competition strengthens the impact of monetary policy on bank loan supply. We then show that states with a more deregulated banking sector were more affected by monetary conditions in the years leading to the Great Recession. Specifically, the effect of loose monetary conditions on the expansion of households’ debt was stronger in states that had fewer bank branching restrictions. The results suggest that variations in the level of bank competition may have amplified regional asymmetries in the years leading to the Great Recession.